Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Certainly! Let's simplify the given expression step by step:
Given:
[tex]\[ \left(\frac{3^n \times 9^{n+1}}{3^{n-1} \times 9^{n-1}}\right) \][/tex]
First, we recall that [tex]\(9\)[/tex] can be written as [tex]\(3^2\)[/tex]. Therefore, we can rewrite the expression with base [tex]\(3\)[/tex]:
[tex]\[ 9 = 3^2 \][/tex]
Substituting [tex]\(9\)[/tex] in the expression:
[tex]\[ \left(\frac{3^n \times (3^2)^{n+1}}{3^{n-1} \times (3^2)^{n-1}}\right) \][/tex]
Next, we simplify the exponents. Using the property of exponents [tex]\((a^m)^n = a^{mn}\)[/tex]:
[tex]\[ (3^2)^{n+1} = 3^{2(n+1)} = 3^{2n + 2} \][/tex]
[tex]\[ (3^2)^{n-1} = 3^{2(n-1)} = 3^{2n - 2} \][/tex]
Substituting these back into the expression, we get:
[tex]\[ \left(\frac{3^n \times 3^{2n + 2}}{3^{n-1} \times 3^{2n - 2}}\right) \][/tex]
Using the property of exponents [tex]\(a^m \times a^n = a^{m+n}\)[/tex], we can combine the exponents in the numerator and the denominator:
In the numerator:
[tex]\[ 3^n \times 3^{2n + 2} = 3^{n + 2n + 2} = 3^{3n + 2} \][/tex]
In the denominator:
[tex]\[ 3^{n-1} \times 3^{2n-2} = 3^{(n-1) + (2n-2)} = 3^{n - 1 + 2n - 2} = 3^{3n - 3} \][/tex]
So, the expression simplifies to:
[tex]\[ \left(\frac{3^{3n + 2}}{3^{3n - 3}}\right) \][/tex]
Using the property [tex]\(\frac{a^m}{a^n} = a^{m-n}\)[/tex]:
[tex]\[ 3^{(3n + 2) - (3n - 3)} = 3^{3n + 2 - 3n + 3} = 3^{5} \][/tex]
Finally, calculating [tex]\(3^5\)[/tex]:
[tex]\[ 3^5 = 3 \times 3 \times 3 \times 3 \times 3 = 243 \][/tex]
Thus, the simplified expression is:
[tex]\[ \boxed{243} \][/tex]
Given:
[tex]\[ \left(\frac{3^n \times 9^{n+1}}{3^{n-1} \times 9^{n-1}}\right) \][/tex]
First, we recall that [tex]\(9\)[/tex] can be written as [tex]\(3^2\)[/tex]. Therefore, we can rewrite the expression with base [tex]\(3\)[/tex]:
[tex]\[ 9 = 3^2 \][/tex]
Substituting [tex]\(9\)[/tex] in the expression:
[tex]\[ \left(\frac{3^n \times (3^2)^{n+1}}{3^{n-1} \times (3^2)^{n-1}}\right) \][/tex]
Next, we simplify the exponents. Using the property of exponents [tex]\((a^m)^n = a^{mn}\)[/tex]:
[tex]\[ (3^2)^{n+1} = 3^{2(n+1)} = 3^{2n + 2} \][/tex]
[tex]\[ (3^2)^{n-1} = 3^{2(n-1)} = 3^{2n - 2} \][/tex]
Substituting these back into the expression, we get:
[tex]\[ \left(\frac{3^n \times 3^{2n + 2}}{3^{n-1} \times 3^{2n - 2}}\right) \][/tex]
Using the property of exponents [tex]\(a^m \times a^n = a^{m+n}\)[/tex], we can combine the exponents in the numerator and the denominator:
In the numerator:
[tex]\[ 3^n \times 3^{2n + 2} = 3^{n + 2n + 2} = 3^{3n + 2} \][/tex]
In the denominator:
[tex]\[ 3^{n-1} \times 3^{2n-2} = 3^{(n-1) + (2n-2)} = 3^{n - 1 + 2n - 2} = 3^{3n - 3} \][/tex]
So, the expression simplifies to:
[tex]\[ \left(\frac{3^{3n + 2}}{3^{3n - 3}}\right) \][/tex]
Using the property [tex]\(\frac{a^m}{a^n} = a^{m-n}\)[/tex]:
[tex]\[ 3^{(3n + 2) - (3n - 3)} = 3^{3n + 2 - 3n + 3} = 3^{5} \][/tex]
Finally, calculating [tex]\(3^5\)[/tex]:
[tex]\[ 3^5 = 3 \times 3 \times 3 \times 3 \times 3 = 243 \][/tex]
Thus, the simplified expression is:
[tex]\[ \boxed{243} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.